吉非替尼对比培美曲塞二线治疗晚期非鳞型非小细胞肺癌的随机对照临床研究 (Zhongguo Fei Ai Za Zhi, 2013)
BACKGROUND AND OBJECTIVE: Geftinib and Pemetrexed are drugs used as second-line therapy for advanced non-small cell lung cancer (NSCLC), although studies comparing the two drugs are limited. The aim of this study is to explore the effects, safety, and quality of life (QoL) of Geftinib and Pemetrexed on patients with advanced non-squamous NSCLC. METHODS: Forty-six advanced non-squamous NSCLC patients who failed to frst-line therapy were randomly divided into two groups with 23 patients each, one using oral Geftinib (Geftinib group) and the other using intravenous injection Pemetrexed (Pemetrexed group). The effects, safety, and QoL were determined and analyzed. RESULTS: For the Pemetrexed group, objective response rate (ORR) was 13.0% (3/23), disease control rate (DCR) was 30.4% (7/23), and median progression-free survival (mPFS) was 3.1 months. In the Geftinib group, ORR was 17.3% (4/23), DCR was 39.1% (9/23), and mPFS was 4.4 months. Compared with the Pemetrexed group, the ORR, DCR, and mPFS in the Geftinib group exhibited no statistical signifcance (P > 0.05). Furthermore, the most common toxicities in the Pemetrexed group were neutropenia (n=9, 39.13%) and fatigue (n=8, 34.78%), whereas those in the in Geftinib group were skin rash (n=8, 34.78%) and diarrhea (n=4, 17.39%). Compared with baseline, the QoL improved in both groups but to different degrees. Likewise, emotional, functional wellbeing, and QoL aspects specifcally related to lung cancer were beter improved in the Geftinib group than in the Pemetrexed group (P < 0.05). CONCLUSION: The effects of Pemetrexed and Geftinib as second line therapy were similar, although with different AEs. Both drugs could improve the QoL, but Geftinib showed beter overall results than Pemetrexed.